Comprehensive Understanding of Slow Learners (Borderline Intellectual Functioning) - Cheon, Keun-Ah (Journal of the Korean Academy of Child and Adolescent Psychiatry, 2024)
The World Health Organization’s International Classification of Diseases (ICD) also recognizes this condition and provides a framework for understanding and support. [...]their cognitive abilities allow them to perform daily tasks and meet basic social and personal care demands independently, distinguishing them from individuals with significant intellectual disabilities. Community support, including inclusive activities and social groups, can enhance social integration and emotional wellbeing [2].